IMPLEMENTASI KEBIJAKAN RELOKASI PASAR TRADISIONAL DELI TUA KABUPATEN DELI SERDANG - Dara Aisyah; Marissa Claudia Pangaribuan (Smart Education, 2023)
Abstract: The Deli Tua traditional market relocation policy is a policy based on Deli Serdang Regency Regent Regulation No. 688 of 2012 concerning Management of Traditional Markets, Shopping Centers and Modern Stores. The purpose of the Deli Tua market relocation is for spatial planning and building a new market building that can provide a sense of comfort and security for traders and buyers. The method used is a descriptive method with a qualitative approach. Data collection techniques were carried out by means of interviews, observations and documentation related to the implementation of the Deli Tua traditional market relocation policy, Deli Serdang Regency. The results showed that the implementation of the Deli Tua Market relocation policy experienced problems due to the refusal by traders. Therefore, the researcher analyzes the implementation of the Deli Tua Market relocation policy using the Van Meter and Van Horn implementation model which includes standard and objectives, resources, communication among implementers, attitude of implementers and social, economic and political conditions. The researcher found that the obstacles occurred in human resources who lacked knowledge about market relocation, then there was no socialization to traders so that traders were not involved in the construction of new market.Keywords: policy implementation; relocation; traditional market Abstrak: Kebijakan relokasi pasar tradisional Deli Tua merupakan kebijakan berdasarkan Peraturan Bupati Deli Serdang Nomor 688 Tahun 2012 tentang Pengelolaan Pasar Tradisional, Pusat Perbelanjaan dan Toko Modern. Tujuan relokasi pasar Deli Tua adalah untuk penataan ruang dan pembangunan pasar yang dapat memberikan rasa aman dan nyaman bagi pedagang dan pembeli. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Peneliti menemukan kendalan terjadi pada SDM yang kurang memiliki pengetahuan tentang relokasi pasar, kemudian tidak adanya sosialisasi kepada pedagang sehingga pedagang tidak dilibatkan dalam pembangunan pasar baru. Hasil penelitian menunjukan bahwa pelaksanaan kebijakan relokasi pasar tradisional Deli Tua menggunakan model implementasi Van Meter dan Van Horn yang meliputi standar dan tujuan, sumber daya, komunikasi antar pelaksana, sikap pelaksana, dan kondisi sosial, ekonomi dan politik.Kata kunci: implementasi kebijakan; relokasi; pasar tradisional